Answer :

As we know, n^{th} term in A.P. is a + (n-1)d

Where, a is first term

n is Nth term

d is difference between terms

Given in one sequence, a_{1}=63 and d_{1}=2

In the other sequence, a_{2}=3 and d_{2}=7

Given n^{th} term of both A.Ps are equal

So, a_{1}+(n-1)d_{1}=a_{2} +(n-1)d_{2}

⇒63+(n-1)2=3+(n-1)7

⇒61+2n=-4+7n

⇒65=5n

⇒n=13

Conclusion: Therefore, for n = 13 it is equal.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Glimpses of India39 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation